Facilitate cross-selling of value-added mobile services using data mining - Hamidreza Atefi (مدیریت مهندسی و رایانش نرم)
Gaining a competitive advantage is very important for mobile operators. Mobile value-added services are one of the innovations that operators use to diversify their business. Cross-selling is crucial for mobile operators to generate revenue and profits. Because operators will incur lower ancillary costs compared to attracting new customers. But it is not easy for them to identify potential customers who buy the services provided by operators. In this article, an attempt has been made to facilitate the cross-selling of mobile value-added services. The data used in this research is information about the past purchases of the customers of HamrahAval Company from the value-added mobile services. In the proposed solution, the infrastructure for creating cross-selling customer profiles is discussed. In this solution, after determining the optimal category of customers using their clustering, an attempt has been made to discover the rules between the services used by customers. By creating this profile, a target community can be achieved for the cross-selling of each service.